The Electronic Chart Display and Information System (ECDIS) in China - , The Research Group on ECDIS (The International Hydrographic Review, 2018)
This paper presents a prototype of ECDIS developed by the Research Group on ECDIS of the Dalian Maritime University, China, and describes briefly the configuration, function and characteristics of this system. Trials ashore and at sea have proved the good performance of the system.